A brief transdiagnostic group (the take control course) compared to individual low-intensity CBT for depression and anxiety: a randomized non-inferiority trial. Issue 3 (4th May 2023) - Morris, Lydia; Lovell, Karina; McEvoy, Phil; Emsley, Richard; Carter, Lesley-Anne; Edge, Dawn; Bates, Rachel; Wallwork, Tanya; Mansell, Warren
ABSTRACT: Few studies have examined brief transdiagnostic groups. The Take Control Course (TCC) was developed for patients with mild to moderate common mental health problems. We examined whether TCC is non-inferior to individual low-intensity cognitive behaviour therapy (CBT) in a single-blind individually randomised parallel non-inferiority trial. The primary outcomes were depression (PHQ9) and anxiety (GAD7) at 6-month follow-up (primary outcome point) and 12-month follow-up. The non-inferiority margin that we set, based on previous trials, corresponds to approximately 3 points on the PHQ9 and approximately 2.5 points on the GAD7. Intention-to-treat (ITT) and per-protocol (PP) analyses of 6-month data of 156 randomised patients indicated that TCC was non-inferior to individual low-intensity CBT on anxiety (ITT Coefficient = 0.24; 95% CI: −1.45 to 1.92; d  = 0.04; p  = .79), and depression (ITT Coefficient = 0.82; 95% CI: −1.06 to 2.69; d  = 0.14; p  = .39) outcomes, and functioning (ITT Coefficient = 0.69; 95% CI: −2.56 to 3.94; d  = 0.08; p  = .68). The findings at 12 months were inconclusive and require further testing. This randomised trial provides preliminary support that TCC is not less effective than short-term individual CBT within Improving Access to Psychological Therapies (IAPT) services.